HO-3867 Induces ROS-Dependent Stress Response and Apoptotic Cell Death in Leishmania donovani - Das, Amrita; Kamran, Mohd.; Ali, Nahid (Frontiers in Cellular and Infection Microbiology, 2021)
Lack of vaccine and increasing chemotherapeutic toxicities currently necessitates development of effective and safe drugs against various forms of leishmaniases. We characterized the cellular stress induced by a novel curcumin analogue, HO-3867, encapsulated within phosphatidylcholine-stearylamine (PC-SA) liposome for the first time against Leishmania. Liposomal formulation of HO-3867 (i.e. PC-SA/HO-3867) initiated oxidative stress induced apoptosis in L. donovani, revealed by altered cell morphology, phosphatidylserine externalization, mitochondrial depolarization, intracellular lipid accumulation and cell cycle arrest in promastigotes. Liposomal HO-3867 was observed to be a strong apoptosis inducer in L. donovani and L. major in a dose dependent manner, yet completely safe for normal murine macrophages. Moreover, PC-SA/HO-3867 treatment induced L. donovani metacaspase and PARP1 activation along with down-regulation of Sir2 gene. PC-SA/HO-3867 arrested intracellular L. donovani amastigote burden in vitro, with reactive oxygen species (ROS) and nitric oxide (NO)-mediated parasite killing. These data suggest that liposomal HO-3867 represents a highly promising and non-toxic nanoparticle-based therapeutic platform against leishmaniasis inspiring further preclinical developments.